Compartement Analysis of Reservoir X Uses Dynamic Data and Geology Data in ND Structure, South Sumatera - Nida Muthia Lamis; Suryo Prakoso; Rini Setiati (Journal of Earth Energy Science, Engineering, and Technology, 2020)
The ND Structure is located in the South Sumatra Basin, which is located in the ND Block. The ND Structure is located in the South Sumatra Basin, South Sumatra Province. This Structure is the southern part of the South Sumatra Basin onshore.The reservoir x compartmentalization analysis is carried out using the fault seal analysis method, mapping the reservoir x property combined with the analysis of pressure data between compartments. Combining the method between fault seal analysis, history of pressure trend analysis and mapping of subsurface properties can be used as a method to explain and describe reservoir compartment. Reservoir connectivity of Reservoir X separated by faults and property barriers in ND Structure, so from the analysis that reservoir X is divided into 4 (four) compartments.